Therapeutic effects of the allosteric protein tyrosine phosphatase 1B inhibitor KY-226 on experimental diabetes and obesity via enhancements in insulin and leptin signaling in mice - Yuma Ito; Masaki Fukui; Mamoru Kanda; Ko Morishita; Yoshimichi Shoji; Tatsuya Kitao; Eiichi Hinoi; Hiroaki Shirahase (Elsevier, 2018)
The anti-diabetic and anti-obesity effects of the allosteric protein tyrosine phosphatase 1B (PTP1B) inhibitor 4-(biphenyl-4-ylmethylsulfanylmethyl)-N-(hexane-1-sulfonyl)benzoylamide (KY-226) were pharmacologically evaluated. KY-226 inhibited human PTP1B activity (IC50 = 0.28 μM), but did not exhibit peroxisome proliferator-activated receptor γ (PPARγ) agonist activity. In rodent preadipocytes (3T3-L1), KY-226 up to 10 μM had no effects on adipocyte differentiation, whereas pioglitazone, a PPARγ agonist, markedly promoted it. In human hepatoma-derived cells (HepG2), KY-226 (0.3-10 μM) increased the phosphorylated insulin receptor (pIR) produced by insulin. In db/db mice, the oral administration of KY-226 (10 and 30 mg/kg/day, 4 weeks) significantly reduced plasma glucose and triglyceride levels as well as hemoglobin A1c values without increasing body weight gain, while pioglitazone exerted similar effects with increases in body weight gain. KY-226 attenuated plasma glucose elevations in the oral glucose tolerance test. KY-226 also increased pIR and phosphorylated Akt in the liver and femoral muscle. In high-fat diet-induced obese mice, the oral administration of KY-226 (30 and 60 mg/kg/day, 4 weeks) decreased body weight gain, food consumption, and fat volume gain with increases in phosphorylated STAT3 in the hypothalamus. In conclusion, KY-226 exerted anti-diabetic and anti-obesity effects by enhancing insulin and leptin signaling, respectively. Keywords: PTP1B inhibitor, Diabetes, Obesity, Allosteric inhibitor, db/db mouse